Functionalization of MWCNTs with atomic nitrogen - Ruelle, Benoit; Felten, Alexandre; Ghijsen, Jacques; Drube, Wolfgang; Johnson, Robert L.; Liang, Duoduo; Erni, Rolf; Van Tendeloo, Gustaaf; Sophie, Peeterbroeck; Dubois, Philippe; Godfroid, Thomas; Hecq, Michel; et al. (Micron (Oxford, England : 1993), 2009)
In this study of the changes induced by exposing MWCNTs to a nitrogen plasma, it was found by HRTEM that the atomic nitrogen exposure does not significantly etch the surface of the carbon nanotube (CNT). Nevertheless, the atomic nitrogen generated by a microwave plasma effectively grafts amine, nitrile, amide, and oxime groups onto the CNT surface, as observed by XPS, altering the density of valence electronic states, as seen in UPS.